Validation of a molecular risk score for prognosis of patients with acute promyelocytic Leukemia treated with all-trans retinoic acid and chemotherapy-containing regimens - Hecht, Anna; Doll, Seraphina; Nowak, Daniel; Lengfelder, Eva; Weiß, Christel; Hofmann, Wolf-Karsten; Nolte, Florian (Clinical lymphoma, myeloma & leukemia, 2017)
Introduction: Although treatment of acute promyelocytic leukemia (APL) has evolved dramatically during the past decades, especially with the introduction of all-trans retinoic acid, risk stratification remains an important issue. To date, relapse risk can be predicted by leukocyte and platelet counts only. In the present report, we present a validation study on 3 candidate genes and a newly developed molecular risk score for APL in 2 independent patient cohorts. Patients and Methods: An integrative risk score combining the expression levels of BAALC, ERG, and WT1 was calculated for 79 de novo APL patients from the original cohort and 76 de novo APL patients from a validation cohort. Gene expression analysis was executed the same for both cohorts, and the results regarding the effect on patient outcomes were compared. Results: The expression levels of BAALC, ERG, and WT1 were similar in both cohorts compared with the healthy controls. The relapse and survival rates were not different between the low- and high-risk patients according to the Sanz score. However, application of the molecular risk score on the validation cohort distinctly discriminated patients according to their risk of relapse and death just as in the original APL cohort, although single gene analyses could not reproduce the negative prognostic impact. Conclusion: The analysis clearly validated the prognostic effect of the integrative risk score on the outcome in APL patients. The value was further empowered because the single gene analyses did not show similar results. Whether the integrative risk score retains its prognostic power in the chemotherapy-free setting should be investigated further.